Impact of sentiment and monetary policy on Mexican tourism stock returns: the domestic and US role - Irani, Farid; Hadood, Abobaker Al Al; Katircioglu, Salih; Katircioglu, Setareh (Emerald Group Publishing Ltd, 2023)
Purpose - This paper focuses on the role of sentiment and monetary policy (both domestic and the United States (US)) in explaining the changes in the Mexican tourism firms' stock returns for the period 1998M03-2019M12. Design/methodology/approach - The authors conducted the ordinary least square regression estimations using various models to investigate the impact of sentiment and monetary policy changes on tourism firms' stock returns. Furthermore, to provide a robust check, the authors run all regression models based on the capital asset pricing model by regressing the excess returns of tourism firms' stocks on all independent variables. Findings - Empirical findings reveal that the changes in Mexican consumer sentiment have a stronger positive effect on tourism firms' stock returns than Mexican business sentiment changes. However, the US consumer and business sentiment are irrelevant to tourism firms' stock returns. Moreover, this study's results indicate that changes in the US interest rates positively influence tourism firms' stock returns. This study's findings show that as the monetary divergence between Mexico and the US (differential real interest rates) widens, the lower is the tourism firms' stock returns. Originality/value - This study is the first to extend the prior studies by examining the effects of sentiment and monetary policy (both domestic and US role) on Mexican tourism stock return.
Keywords: Sentiment; Monetary policy; US spillover effect; Mexican tourism; Stock returns